Mechanical Properties of High Impact Polystyrene/ Styrene-Butadiene-Styrene Blends - Samsudin, Sani Amril (2004)

(untitled)
Blends of High Impact Polystyrene (HIPS) with Styrene-Butadiene-Styrene (SBS) have two important applications include restoring the impact resistance, which is lost when flame-retardants are mixed into HIPS, and upgrading HIPS to a super high impact product. The purpose of this research is to study the effect of SBS (TR2000) composition on the mechanical properties of HIPS/SBS blends. The measurement of mechanical properties of HIPS/SBS blends has been made at various compositions. Using a single screw extruder, blends of HIPS/SBS with SBS compositions ranging from 0-12 phr were prepared and the specimens for mechanical evaluations were injection-molded. The mechanical test such as tensile test, flexural test, and impact test were carried out. Incorporation of rubbers in the blends increases Izod impact strength. On the other hand, tensile strength and flexural modulus were decrease with increasing the composition of SBS.